2020
DOI: 10.1186/s12864-020-07260-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal salt stress-induced transcriptome alterations and regulatory mechanisms revealed by PacBio long-reads RNA sequencing in Gossypium hirsutum

Abstract: Background Cotton (Gossypium hirsutum) is considered a fairly salt tolerant crop however, salinity can still cause significant economic losses by affecting the yield and deteriorating the fiber quality. We studied a salt-tolerant upland cotton cultivar under temporal salt stress to unfold the salt tolerance molecular mechanisms. Biochemical response to salt stress (400 mM) was measured at 0 h, 3 h, 12 h, 24 h and 48 h post stress intervals and single-molecule long-read sequencing technology fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…For example, a transcriptome analysis of a salt-tolerant cotton cultivar (Gossypium hirsutum) under temporal salt stress, has identified differentially expressed genes that -similar to our studywere mainly related to stress pathways such as "response to oxidative stress", "response to salt stress", "response to water deprivation", "ion transport", and "metal ion transport". Differently expressed genes related to ion homeostasis, transcription factors and cell wall modification were also found highly active in response to salt stress in cotton same as our study [76]. Studying transcriptome changes under salt stress in Populus wutunensis which is a salt and drought tolerant species, differentially expressed genes were identified in salt treated leaves that were also involved in ion transport, osmotic regulation, and reactive oxygen species (ROS) scavenging [13].…”
Section: Discussionsupporting
confidence: 76%
“…For example, a transcriptome analysis of a salt-tolerant cotton cultivar (Gossypium hirsutum) under temporal salt stress, has identified differentially expressed genes that -similar to our studywere mainly related to stress pathways such as "response to oxidative stress", "response to salt stress", "response to water deprivation", "ion transport", and "metal ion transport". Differently expressed genes related to ion homeostasis, transcription factors and cell wall modification were also found highly active in response to salt stress in cotton same as our study [76]. Studying transcriptome changes under salt stress in Populus wutunensis which is a salt and drought tolerant species, differentially expressed genes were identified in salt treated leaves that were also involved in ion transport, osmotic regulation, and reactive oxygen species (ROS) scavenging [13].…”
Section: Discussionsupporting
confidence: 76%
“…Salinity reduces crop yield, and decreases the quality of agricultural products e.g. seeds, fruits, and fibre [ 2 4 ]. Given the fact that breeding salt tolerant crop species is a time-consuming program and the practical approach such as irrigating saline soil with fresh water is not affordable in many areas, especially the semi-arid area, techniques which can help to improve crop salt tolerance in the production period could be an option for farming practice.…”
Section: Introductionmentioning
confidence: 99%
“…These unigenes were homologues of genes that are known to contribute to oxidative stress tolerance ( Table S32 ). A transcriptome study of a salt tolerant cotton variety ( Gossypium hirsutum ) has reported differentially expressed genes from the BP category of “response to oxidative stress” as well [ 40 ]. Another gene expression study in a salt tolerant plant ( Suaeda salsa ) also has shown differentially expressed genes involved in the BP category of reactive oxygen species (ROS) scavenging [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The homologous genes of those unigenes are known to encode for proteins that guard the plant against pathogens ( Table S32 ). Pathogens have been suggested to be one of the main biotic stressors for mangrove trees in their natural habitats [ 8 , 12 ] which is also seen in other plant species such as cotton ( Gossypium hirsutum ) [ 8 , 40 ]. Furthermore, large families of MAPK (mitogen-activated protein kinase) pathway components in plants are known to be activated in response to stressors such as salt, drought, heat, and wounding [ 42 ].…”
Section: Discussionmentioning
confidence: 99%